A 2-D dysprosium glutarate exhibiting slow magnetic relaxation and luminescent properties. Issue 16 (17th September 2018) - Liu, Xing; Zhou, Jian; Zou, Hua-Hong; Fu, Lianshe
Abstract: A 2-D dysprosium glutarate [Dy2 (glu)3 (phen)2 ]n (1, glu = glutarate, phen =1, 10-phenanthroline) has been synthesized from the hydrothermal reaction of DyCl3, glutaric acid, and phen ligand. Compound1 displays a classical 2-D (4, 4) grid structure constructed by the linkages of Dy 3+ ions and three types of glutarate ligands. Compound1 shows slow magnetic relaxation and luminescent properties. Although some lanthanide glutarates have been reported, they do not exhibit slow magnetic relaxation properties. Compound1 offers the only example of a dysprosium coordination polymer with field-induced single-molecule magnets (SMMs) based on aliphatic dicarboxylic acids in the absence of ancillary aromatic carboxylic acids. Abstract : This work offers the only example of a dysprosium coordinatination polymer with field-induced SMM based on aliphatic dicarboxylic acids without aromatic carboxylic acids.